Characteristics of Adults Aged 18–49 Years Without Underlying Conditions Hospitalized With Laboratory-Confirmed Coronavirus Disease 2019 in the United States: COVID-NET—March–August 2020. (3rd December 2020) - Owusu, Daniel; Kim, Lindsay; O'Halloran, Alissa; Whitaker, Michael; Piasecki, Alexandra M; Reingold, Arthur; Alden, Nisha B; Maslar, Amber; Anderson, Evan J; Ryan, Patricia A; Kim, Sue; Como-Sabetti, Kathryn; et al.
Abstract: Among 513 adults aged 18–49 years without underlying medical conditions hospitalized with coronavirus disease 2019 (COVID-19) during March 2020–August 2020, 22% were admitted to an intensive care unit, 10% required mechanical ventilation, and 3 patients died (0.6%). These data demonstrate that healthy younger adults can develop severe COVID-19.